INVESTIGATING ENGLISH LEARNING MOTIVATION BY APPLYING GAME ELEMENT - Waode Hamsia (LPPM Universitas PGRI Jombang, 2025)
This research aimed to analyze how first semester students in Early Childhood Education Program at Universitas Muhammadiyah Surabaya were motivated through the Quizizz game-based learning method. Using a descriptive qualitative method, data were gathered via observation, questionnaires, and interviews. The findings indicated that Quizizz enhanced motivation by fostering enjoyment, engagement, and concentration. The research concluded that while Quizizz temporarily increases enthusiasm, sustained motivation requires diverse learning approaches and active lecturer facilitation.